2012
DOI: 10.1101/gr.134635.111
|View full text |Cite
|
Sign up to set email alerts
|

MuSiC: Identifying mutational significance in cancer genomes

Abstract: Massively parallel sequencing technology and the associated rapidly decreasing sequencing costs have enabled systemic analyses of somatic mutations in large cohorts of cancer cases. Here we introduce a comprehensive mutational analysis pipeline that uses standardized sequence-based inputs along with multiple types of clinical data to establish correlations among mutation sites, affected genes and pathways, and to ultimately separate the commonly abundant passenger mutations from the truly significant events. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
569
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 607 publications
(571 citation statements)
references
References 38 publications
1
569
0
1
Order By: Relevance
“…Approximately 20% of the 217 tumors were hypermutated (>12 mutations per 10 6 bases) (43), and the eight SAMHD1 mutations (Table S1) were found in these hypermutated tumors. Analysis of the dataset using the Significantly Mutated Genes (SMG) test from the MuSIC suite (44) showed that-when taking into consideration mutation type and gene length-SAMHD1 carried more mutations than expected by chance (P = 0.049, false discovery rate = 0.05, convolution test).…”
Section: Samhd1mentioning
confidence: 99%
“…Approximately 20% of the 217 tumors were hypermutated (>12 mutations per 10 6 bases) (43), and the eight SAMHD1 mutations (Table S1) were found in these hypermutated tumors. Analysis of the dataset using the Significantly Mutated Genes (SMG) test from the MuSIC suite (44) showed that-when taking into consideration mutation type and gene length-SAMHD1 carried more mutations than expected by chance (P = 0.049, false discovery rate = 0.05, convolution test).…”
Section: Samhd1mentioning
confidence: 99%
“…In contrast, somatic mutations are often neither specific nor sensitive for a particular type of cancer. Even within commonly mutated genes, individual mutations may be found across tens or hundreds of kilobases, limiting the utility of targeted sequencing of molecular markers (10,13,14).…”
mentioning
confidence: 99%
“…However, although variations in the observed frequency of SNPs will arise from the positive/negative selection of somatic mutations, they may also be intrinsic (germline-derived), making their functional significance at different sites difficult to assess (19,20) (Fig. S1).…”
mentioning
confidence: 99%